Prevalence, level and factors associated with malnutrition in children under-five years of age and their parents' awareness about children nutrition in Quetta city - Musa Bin Bashir; Muqadim Sadiq; Mirwais Khan; Asad Khan; Adlin Ho; Syed Muhammad Younas (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2021)
Background: Malnutrition continues to be a major public health problem in developing countries. It is the most important risk factor for the burden of diseases. There was lack of information regarding the prevalence, level and factors associated with malnutrition among children of under-five years of age from Baluchistan, Pakistan.  Objective: Therefore, the current study was conducted to evaluate the prevalence, associated factors and parents' awareness with malnutrition among children of under-five years of age.  Methods: This cross-sectional analytical study was carried out at Basic Health Unit (BHU), Nawa Killi, BHU Killi Deba, BHU Spini Road, Mubarak Chowk, Sheikh Zahid Hospital Quetta, Rehnuma Center Satellite Town Quetta. A self-developed validated questionnaire was used to evaluate the parents' awareness regarding children nutrition status. The mean mid upper-arm circumference (MUAC) value of the children was used to categorize the children nutritional status. Children with MUAC value < 12 cm were classified as malnourished, MUAC value =11-12 cm was considered as Moderate Acute Malnutrition (MAM) and, MUAC value < 11 cm was considered as Severely Acute Malnutrition (SAM). Data was analyzed by using Statistical Package for Social Sciences (SPSS version 20). Multivariate binary logistic regression was used to find factors associated with the presence of malnutrition. A p-value <0.05 was considered statistically significant.  Results: A total of 205 children and their parents were included in the study. Majority of studied children were baby boys (60.4%) and belonged to the age group of 0-12 months (74.6%). Majority of the fathers of evaluated children were laborers (42%) and had a family monthly income of between 10000-20000 Pakistani Rupees. Majority of respondents were not well-known about the colostrum milk (63.9%), had not been informed or taught about nutrition (73.7%) and considered children vaccination necessary of disease prevention (91.7%), and had vaccinated their children (97.1%). prevalence of malnutrition in children who were not breastfed was 55.99 times higher than those who were breast fed (p-value <0.001, OR=55.99, 95%CI=13.524-231.842). Conclusion: The undernutrition in children is comparable to the national figures. Although our study found that absence of formal education, big family size, late and early weaning, absence of exclusive breast feeding and poverty were the factors associated with undernutrition in children, they could cause increase in under nutrition in future if not improved.